World watch geography book 2 - Moorcroft, Christine (Oxford university press: Karachi, 2023)
"World Watch Geography Book 2" for Grade 7 covers key aspects of physical and human geography. It explores Earth's features, ecosystems, natural phenomena, population dynamics, economic activities, and cultural diversity. The book emphasizes real-world applications and addresses global environmental challenges like deforestation and climate change, fostering critical thinking and geographic skills.